ANALISIS HUBUNGAN PRODUKSI PERIKANAN TANGKAP LAUT, CURAH HUJAN, DAN SUHU PERMUKAAN LAUT DENGAN MODEL VECTOR AUTOREGRESSIVE (VAR) - RAMLI, RAMADHAN LENGGU; SUMARJAYA, I WAYAN; SARI, KARTIKA (E-Jurnal Matematika; Vol 8 No 2 (2019)DO - 10.24843/MTK.2019.v08.i02.p247, 2019)
NTT Province is one of the provinces with the largest marine ca tch fisheries production in Indonesia. Rainfall and sea surface temperature are factors that affect marine ca tch fisheries production. This study aims to analyze relationships between marine ca tch fisheries production, sea surface temperature and rainfall in NTT based on time series data using a vector autoregressive model (VAR). The result of this study : (i) the best VAR model for forecasting marine ca tch fisheries, rainfall, and sea surface temperature is a second-order VAR model (VAR (2)), (ii) based on MAPE forecasting criteri on , the VAR model obtained classified as good forecasting for variable production of marine ca tch fisheries, and sea surface temperature, while for rainfall forecasting is inaccurate, (iii) significant sea surface temperatures affect marine ca tch fisheries production and rainfall in NTT.